A Prospective Pilot Study for Prognosis of Cardiac Resynchronization Therapy Super-Response Using Electrical and Mechanical Dyssynchrony Assessment in Patients with Heart Failure and Strauss Left Bundle Branch Block Criteria - Tariel Atabekov; Andrey Smorgon; Anna Mishkina; Sergey Krivolapov; Svetlana Sazonova; Mikhail Khlynin; Roman Batalov; Sergey Popov (Life)
Electrical and mechanical dyssynchrony (MD) underlies left ventricular (LV) contractile dysfunction in patients with heart failure (HF) and left bundle branch block (LBBB). In some cases, cardiac resynchronization therapy (CRT) almost completely reverses LV contractile dysfunction. The LBBB electrocardiographic Strauss criteria and MD assessment were proposed to improve CRT response. However, using these techniques separately does not improve LV contraction in 20–40% of patients after CRT device implantation. We aimed to evaluate whether the combined use of electrocardiography (ECG), speckle-tracking echocardiography (STE) and cardiac scintigraphy could improve the prognosis of CRT super-response in patients with HF and Strauss LBBB criteria during a 6-month follow-up period. The study prospectively included patients with HF, classified as New York Heart Association (NYHA) functional class (FC) II–III in sinus rhythm with Strauss LBBB criteria and reduced left ventricular ejection fraction (LVEF). Before and 6 months after CRT device implantation, ECG, STE and cardiac scintigraphy were performed. The study’s primary endpoint was the NYHA class improvement ≥ 1 and left ventricle end systolic volume decrease > 30% or LVEF improvement > 15% after 6 months of CRT. Based on collected data, we developed a prognostic model regarding the CRT super-response. Out of 54 (100.0%) patients, 39 (72.2%) had a CRT super-response. Patients with CRT super-response were likelier to have a greater S wave amplitude in V2 lead (p = 0.004), higher rates of global longitudinal strain (GLS) (p = 0.001) and interventricular delay (IVD) (p = 0.005). Only three indicators (S wave amplitude in V2 lead, GLS and IVD) were independently associated with CRT super-response in univariable and multivariable logistic regression. We created a prognostic model based on the logistic equation and calculated a cut-off value (>0.73). The resulting ROC curve revealed a discriminative ability with an AUC of 0.957 (sensitivity 87.2%; specificity 100.0%). The electrical and mechanical dyssynchrony assessment using ECG, STE and cardiac scintigraphy is useful in the prediction of CRT super-response in patients with HF and Strauss LBBB criteria during a 6-month follow-up period. Our prognostic model can identify patients who are super-responders to CRT.